Architectural narratives and spatial language: a discourse study of traditional house descriptions in indonesia - Daroji (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Traditional houses in Indonesia embody complex interrelations between physical architecture, cultural narratives, and spatial language, making them vital subjects for understanding how heritage is materially and discursively preserved. Objective: This study aims to examine how spatial terms, orientations, and symbolic references in descriptions of Rumah Gadang, Tongkonan, and Lopo encode and transmit cultural meaning. Method: Using a qualitative multiple-case study design, the research integrates Spatial Discourse Analysis, Ethnographic Discourse Analysis, and Critical Discourse Analysis to analyze ethnographic texts, museum materials, and archival interviews. Results: The findings reveal that spatial orientations—such as east–west moral polarities, central zones as harmony spaces, and north-facing cosmological alignments—serve as discursive mechanisms for reinforcing social hierarchy, gender roles, and ancestral authority. Cross-case comparison shows that while each house type manifests unique cultural markers, all employ spatial discourse to sustain intangible heritage and legitimize custodianship. Furthermore, the analysis demonstrates how institutional mediation and tourism framing can recontextualize these narratives, sometimes diluting their original meaning. The results underscore the need for heritage preservation strategies that safeguard both physical structures and the narrative vocabularies that animate them. Implication: This research has implications for culturally responsive heritage policy, inclusive museum interpretation, and participatory conservation practices. Novelty: This study shows how spatial discourse functions as a key mechanism through which architectural forms encode, sustain, and negotiate cultural meaning across different Indonesian traditional houses.